THE SEARCH FOR NEW BACTERIA-DESTRUCTORS OF ORGANOCHLORINES OF THE GROUP «PERSISTENT ORGANIC POLLUTANTS», PROMISING FOR THE DEVELOPMENT OF INNOVATIVE ECOBIOTECHNOLOGIES - Egorova, D.O.; Andreev, D.N.; Korsakova, E.S.; Pjankova, A.A.; Maksimov, A.S.; Vasjanin, A.N.; Degtev, M.I. (Perm Federal Research Centre Journal, 2016)
Soil samples from regions with a various technogenic load were analyzed in this paper. A more detailed study of microbial composition of soil samples from «Osinskaya lesnaja dacha» and from the town of Chapayevsk, Samara Oblast is studied. The associations of aerobic bacteria, effectively decomposing DDT and lindane, were obtained. The strains, capable of degrading several compounds of POPs, were singled out. It was established that the introduction of the culture strain Rhodococcus wratislaviensis Ch628 into the soil reduces the concentrations of the main pollutants (DDT, lindane and other hexachlorocyclohexane isomers) and leads to an effective reduction of soil toxicity levels for plants and animals.